Pengaruh PENGARUH VIDEO INTERAKTIF BERBASIS LUMI EDUCATION TERHADAP KETERAMPILAN MENYIMAK PADA PEMBELAJARAN IPAS SISWA KELAS III SDN WORA: VIDEO INTERAKTIF LUMI EDUCATION TERHADAP KEMAMPUAN MENYIMAK PEMBELAJARAN IPAS SISWA - Adianti; Rakhmatul Ummah; Mirham Imamsyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using interactive videos based on Lumi Education on improving listening skills in IPAS learning among third-grade students at SDN Wora. The research employed a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The entire population consisted of 21 third-grade students. The research instruments included pretest and posttest assessments, as well as observation sheets to monitor student activity during the learning process. The results showed a significant improvement in students' IPAS listening skills after using the Lumi Education interactive video. The average pretest score of 41.90 increased to 83.81 on the posttest. Since the data were not normally distributed based on the normality test, the Wilcoxon Signed Ranks Test was used. The test results indicated that all students showed improved learning outcomes without any decline in scores. Additionally, observational data revealed that students were active, enthusiastic, able to understand the content of the video, and confident in expressing their opinions during the learning process. Therefore, the use of Lumi Education-based interactive video media is proven to be effective in enhancing students’ listening skills and can serve as an innovative and engaging alternative for IPAS learning in elementary schools.